The Bible in Arabic - Sidney H. Griffith (Princeton University Press, 2013)
In this era of scholarly specialization, one is intensely aware of his limitations and of his debt to scholars better equipped than he to address even so seemingly simple a topic as the Bible in Arabic. For the fact is that in every chapter that follows one must rely on the work of scholars who have made the particular subject of that chapter the focus of their own studies. To venture into such territory not immediately one’s own does indeed give one pause. Yet the contribution one hopes to make in undertaking the adventure is twofold: first to call attention to the central role the Bible and biblical lore have played in the unfolding of religious thought in Arabic in Islamic times, from Late Antiquity to the Middle Ages; and secondly to highlight the interreligious dimension of intellectual life in the Arabicspeaking world in the same period, even in biblical studies, albeit that it was often a discourse in counterpoint and nothing like the interreligious dialogue of which one speaks so readily in our times. But the fact is that religious and intellectual culture in the World of Islam in the classical period came together in a polyphony of voices in Arabic and the part of the Bible in that chorus, so often actually carrying the melody, has not received the broad recognition it deserves. It is the purpose of the present survey of the available scholarship to call attention to the historical, religious, and cultural importance of the Bible in Arabic, to encourage its continued study, and to provide some bibliographical guidance for the undertaking. In writing this short book I have profited immensely from a semester’s residence at the Hebrew University of Jerusalem’s Institute for Advanced Studies at the invitation of Professor Mordechai Cohen of Yeshiva University and Professor Meir Bar Asher of the Hebrew University. The group they assembled there to study the cross-cultural reading of the Bible in the Middle Ages provided the opportunity for a daily colloquy with a community of scholars for whose counsel and inspiration I am profoundly grateful. Where else in the world could I go just next door to Meir Bar Asher’s office with my problems in Arabic, or down the hall to Meira Polliack for guidance in Judaeo-Arabic and the history of Karaite biblical study, or around the corner to James Kugel for advice on interpretive strategies? Other scholars too have readily given me their help and advice. I thank in particular Prof. Alexander Treiger of Dalhousie University for much advice and bibliographical help, Dr. Ronny Vollandt for sharing with me his just finished and very rich doctoral dissertation on the Pentateuch in Christian Arabic, and Dr. Adam C. McCollum of the Hill Monastic Library in Collegeville, MN, for his very helpful and still growing bibliography of the Bible in Arabic.